Morphology and molecular characterization of a new species of the cate benthic dinoflagellate, coolia malayensis sp. Nov.(dinophyceae) - Chui, P.L; Po, T.L; Kok, W.C; Boon, K.N; Usup, G. (Blackwell Publishing Ltd, 2010)
Coolia Merunier is an important component of benthic dinoflagellate assemblages in tropical and subtropical seas. In this study, detailed morphological observation of Coolia species from Malaysians waters was carried out using light and electron microscopy in parallel with molecular characterization of nuclearencoded partial LSU rDNA, and internal transcribed spacer (ITS) regions.